The Regulation of Corporate Violations: Punishment, Compliance, and the Blurring of Responsibility - Gray, Garry C. (The British journal of criminology, 2006)
In this article, I term the dichotomy that exists over how to regulate corporate violations the punishment model versus compliance school debate'. I then demonstrate that in the area of workplace health and safety, this classic debate on corporate offending has evolved with the shift to regulation through individual responsibility'. This regulatory shift has resulted in a diffusion of responsibility for safety risks as workers have increasingly become individually responsible for enforcing regulation as well as a target of regulation. In essence, workers are being transformed from a victim to a health and safety offender. In this study, I re-conceptualize the role of worker agency in regulatory enforcement by introducing several grounded ethnographic themes, such as the policing of minor violations and the creation of Potemkin Villages, which represent the hidden side' of the local culture of reactions to health and safety enforcement